2011
DOI: 10.1097/psy.0b013e31820a1838
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Crossover and Outcome Predictors in Eating Disorders According to DSM-IV and DSM-V Proposed Criteria: A 6-Year Follow-Up Study

Abstract: Among EDs, there are different subgroups of patients displaying various courses and outcomes. The diagnostic instability involves the large majority of patients. An integration of categorical and dimensional approaches could improve the psychopathological investigation and the treatment choices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
212
4
13

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 235 publications
(253 citation statements)
references
References 52 publications
24
212
4
13
Order By: Relevance
“…The persistent nature of DEB was apparent even at early stages in this longitudinal study: 92% of girls who reported DEB early in the study continued to report it at the 5-year follow-up (18). Consistent with both naturalistic and posttreatment studies of the general population showing persistence but fluctuating severity of eating problems over time (32,(34)(35)(36)(37)(38), substantial rates of remission and recurrent onset were observed across the study period. The course of EDs among the general population, as well as the high prevalence and persistence thus far in this cohort, suggest that clinicians should anticipate that eating disturbances in this population may often be persistent and recurring, rather than mild and transient.…”
Section: Discussionsupporting
confidence: 64%
“…The persistent nature of DEB was apparent even at early stages in this longitudinal study: 92% of girls who reported DEB early in the study continued to report it at the 5-year follow-up (18). Consistent with both naturalistic and posttreatment studies of the general population showing persistence but fluctuating severity of eating problems over time (32,(34)(35)(36)(37)(38), substantial rates of remission and recurrent onset were observed across the study period. The course of EDs among the general population, as well as the high prevalence and persistence thus far in this cohort, suggest that clinicians should anticipate that eating disturbances in this population may often be persistent and recurring, rather than mild and transient.…”
Section: Discussionsupporting
confidence: 64%
“…La mayoría (70,8%) había completado el tratamiento exitosamente y a los 3 años el 41,67% de toda la muestra mostró indicadores de TCA, porcentaje menor que el reportado por otras investigaciones (Castellini et al, 2011;Helverskov et al, 2010;La Mela et al, 2013). El porcentaje de recaída fue del 47,06%, mayor que el encontrado en el estudio de Castellini et al (2011), pero similar al 41% obtenido por Carter et al (2012) en pacientes con AN que siguieron tratamiento de HD.…”
Section: Discussionunclassified
“…Los pacientes con un curso desfavorable de la enfermedad tendieron a mostrar mayor severidad del TCA en la primera evaluación, específicamente puntuaron más alto en el EAT-40 y en la escala DT del EDI-2, lo que concuerda con lo encontrado en otros estudios (Castellini et al, 2011;Helverskov et al, 2010;La Mela et al, 2013). Sin embargo, los sín-tomas psicológicos, según nuestros resultados, no afectan el curso del TCA, confirmando lo señalado por Helverskov et al, (2010), aunque sería importante, en el futuro, evaluar la sintomatología general de modo más amplio que solo con el GSI.…”
Section: Discussionunclassified
See 2 more Smart Citations